(3JWhjQ GdefJLGJ h JSYjQgGs - (3MejO YHO GdfHj(B, (3GdWGFjs; (3GdYdGb HTjQ YHGS(B, s ((3YeGf(B:s (3OGQ GdjGRhQj GdYdejI ddfTQ h GdJhRjY(B,s, 2008)
(3jYQV GdcJGH aj eMJhjGJg eGjdj GdaUd GdChd (B: (3GdefJLGJ GdeaGgje, GdCHYGO, GdBdjGJ hGdGSJQGJjLjGJ (B: (3eGGdebUhO HGdefJL? (B: (3JWHjbGJ GdefJL (B: (3bQGQGJ eRjL GdefJLGJ (B: (3OhQI MjGI GdefJL hGSJQGJjLjGJgG GdJShjbjI (B: (3GdGSJQGJjLjGJ GdJShjbjI deQGMd OhQ MjGI GdefJL (B: (3GdYdGeGJ GdJLGQjI hGdJYHFI hGdJZdja hGdSeGJ GdCNQi (B: (3GdJUeje hGddhf hGdLhOI(B-(3GdaUd GdKGfj (B: (3JWhjQ hGHJcGQ GdefJLGJ GdLOjOI (B: (3eaghe GdJWhjQ hGdGHJcGQ (B: (3CSHGH aTd GdefJLGJ GdLOjOI (B: (3eHQQGJ GHJcGQ GdefJLGJ GdLOjOI hJWhjQgG (B: (3EOGQI GdefJLGJ GdLOjOI (B: (3NWhGJ JWhjQ GHJcGQ GdefJLGJ GdLOjOI(B-(3GdaUd GdKGdK (B: (3GHJcGQ hJWhjQ GdNOeGJ GdLOjOI (B: (3WQb heSGQGJ GdJWhjQ (B: (3GdNWhGJ GdQFjSI GdeJVefI aj YedjI GHJcGQ hJWhjQ hJbOje GdNOeGJ GdLOjOI (B: (3GdYhGed GdeDKQI Ydi YedjI GHJcGQ hJWhjQ GdNOeGJ GdLOjOI (B: (3GHJcGQ hJWhjQ GdNOeGJ GdLOjOI (B: (3NWhGJ JWhjQ GdNOeGJ GdLOjOI (B: (3JMhjd GdSdY Edi NOeGJ hJMhjd GdNOeGJ Edi SdY(B-(3GdaUd GdQGHY (B: (3JSYjQ GdefJLGJ (B: (3GdGYJHGQGJ hGdeOGNd GdJSYQjI (B: (3eONd eaGgjej ddJSYjQ (B: (3GdYhGed GdOGNdjI hGdNGQLjI GdeDKQI aj bQGQGJ GdJSYjQ (B: (3eOGNd GdJSYjQ GdYGeI(B-(3GdaUd GdNGeS (B: (3GdGSJQGJjLjGJ GdJSYjQjI (B: (3GSJQGJjLjGJ GdJSYjQ (B: (3GSJQGJjLjGJ GdJSYjQ GdefJLGJ GdLOjOI (B: (3GSJQGJjLjGJ GdJSYjQ deRjL GdefJLs
(3HjHdjhZQGajG U(B. 207s
Keywords: (3CSYGQs; (3EfJGLs; (3GdEfJGLs; (3JShjbs